2010
DOI: 10.4020/jhrs.26.209
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Ablation of Reentrant Left Ventricular Tachycardia Associated with Fabry disease: A Case Report

Abstract: A 51-year-old man, who was diagnosed with Fabry disease resulting from a kidney biopsy for proteinuria and renal failure in 2002, was admitted to our hospital for sustained ventricular tachycardia (VT). In the electrophysiological study, VT (cycle length: 310 ms) was successfully induced by right ventricle programmed stimulation and the twelve-lead electrocardiogram showed a right bundle branch block configuration with right axis deviation. The mechanism of the VT was considered to be reentry by entrainment ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Because of the small number of cases, we could not statistically analyze the relationship between the type of reentry circuit sites and termination rate, but ablation of isthmus sites (exit, central‐proximal) had a higher rate of termination than nonisthmus sites (inner loop, outer loop). Our results are in agreement with studies that have reported a higher rate of VT termination in exit or central‐proximal segments (30–40%) than in inner loop or outer loop (10%) segments 11,20 . There are differences in opinion, regarding whether inner and outer loop sites should be ablated because of poor termination rate.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Because of the small number of cases, we could not statistically analyze the relationship between the type of reentry circuit sites and termination rate, but ablation of isthmus sites (exit, central‐proximal) had a higher rate of termination than nonisthmus sites (inner loop, outer loop). Our results are in agreement with studies that have reported a higher rate of VT termination in exit or central‐proximal segments (30–40%) than in inner loop or outer loop (10%) segments 11,20 . There are differences in opinion, regarding whether inner and outer loop sites should be ablated because of poor termination rate.…”
Section: Discussionsupporting
confidence: 92%
“…Patients 4 and 5 had normal coronary angiography and diagnosed DCM by findings of left ventricular dilatation and sever reduction of left ventricular ejection fraction using echocardiography and myocardial biopsy. Patient 6 was already diagnosed as having Fabry disease based on his family history, the enzyme activity, and the results of kidney biopsy and genetic evaluation 11 . All 6 patients had inadequate suppression of their VT despite being on oral antiarrhythmics during the study period (amiodarone 1, mexiletine 3, aprindine 2).…”
Section: Resultsmentioning
confidence: 99%
“…In another study, Nakano et al . 10 report on a 51-year-old man with an LVEF of 68%, presenting with SMVT. CMRI demonstrated high T2 signal in the basal epicardium and antero-septal endocardium.…”
Section: Review Of Literaturementioning
confidence: 99%